Consultations in New Prophetic Churches and African Traditional Religions: A Case Study of Divine Healing in Assessing Syncretistic Practices in the South African Context - Kgatle, Mookgo Solomon (Religions, 2023)
New prophetic churches have a different approach to classical Pentecostalism when it comes to the practice of divine healing. Unlike classical Pentecostalism, new prophetic churches embrace the practice of consulting prophets in divine healing in the same way as that in which a traditional healer would be consulted in traditional African religions. During the consultation, the prophet charges a fee and prescribes sacred products that are similar to those of traditional African religious practices. This article uses a case study to illustrate the similarities between new prophetic churches and traditional African religions. Although there are similarities between the two movements, there is a need to also demonstrate their differences. The similarities are framed as continuities, and differences as discontinuities. When diagnosing the problem, a traditional healer throws traditional bones, but a prophet relies on the Holy Spirit to utter a prophetic word. When exorcising a demon causing sickness and diseases, a traditional healer uses rituals to invoke the spirits, but new prophetic churches, with all their weaknesses, would still use the name of Jesus to cast out the evil spirits. The findings in this article have some implications within the theoretical framework of syncretism. The similarities demonstrate syncretistic practices, and the discontinuities demonstrate the nonsyncretistic nature of new prophetic churches in South Africa.